2014
DOI: 10.1186/2052-4374-26-1
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Injury and Socioeconomic Status in Reference to the Fourth Korean National Health and Nutrition Examination Survey

Abstract: ObjectivesThis study aims to investigate the relationship between the total injury experience rate and socioeconomic status based on the fourth Korea National Health and Nutrition Examination Survey (KNHANES).MethodsBy analyzing data from the fourth KNHANES conducted from 2007 to 2009, we estimated the injury experience rate according to socioeconomic status, including the occupational characteristics of 11,837 subjects. Setting the injury experience rate as a dependent variable and socioeconomic status as an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
45
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 42 publications
7
45
2
1
Order By: Relevance
“…These health issues are often less prevalent among individuals with higher socioeconomic status. Furthermore, acquired risk factors for VTE, such as immobilization as a result of physical inactivity or trauma/injury as a result of occupational risks, are less common among the socially advantaged . However, more research is needed to explain which factors are responsible for the decreased risk of venous thromboembolism in higher socioeconomic groups and to identify what interventions could lower the risk in individuals with a lower socioeconomic status.…”
Section: Discussionmentioning
confidence: 99%
“…These health issues are often less prevalent among individuals with higher socioeconomic status. Furthermore, acquired risk factors for VTE, such as immobilization as a result of physical inactivity or trauma/injury as a result of occupational risks, are less common among the socially advantaged . However, more research is needed to explain which factors are responsible for the decreased risk of venous thromboembolism in higher socioeconomic groups and to identify what interventions could lower the risk in individuals with a lower socioeconomic status.…”
Section: Discussionmentioning
confidence: 99%
“…In line with this explanation, blue collar and sales and service workers in South Korea exhibit specific characteristics. Regarding blue collar workers, studies have shown that the occurrence rate of injury-related fatalities is highest in South Korea among OECD countries and that the skilled agricultural, forestry, and fishery workers, craft, equipment, machine operating, and assembling workers, and elementary workers exhibit a higher likelihood of experiencing injuries (S.-K. Kim et al, 2014). When considering that occupational injury is a notable risk factor for depression, with injured workers being more likely to suffer depression, these fundamental characteristics of blue collar workers may serve as a reason for the higher depression scores shown (Asfaw & Souza, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Kim and coworkers [5] found that agriculture workers have higher odds compared to unemployed (OR 1.06, 95% CI 1.03–1.09). However, being employed, a student, and an entrepreneur is significantly associated with lower injury incidence, as opposed to being unemployed.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, Kim and colleagues' [5] and Yiengprugsawan and colleagues' [6] studies found a negative relationship between income and injury experience. Furthermore, poor housing conditions are associated with a broad range of health conditions, including injuries and mental health [7].…”
Section: Introductionmentioning
confidence: 99%